2021
DOI: 10.1016/j.arcmed.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors: Current Use and the Risk of Coronavirus Infectious Disease 2019 Development and its Related Mortality. Meta-analysis

Abstract: Background The ongoing Coronavirus Infectious Disease (COVID-19) pandemic is a global health crisis that has had a magnanimous worldwide impact on all aspects of people's lives. Several observational studies investigated the relationship between Proton Pump Inhibitors use and the risk of COVID-19 development and mortality. Aim of the Study The aim of this meta-analysis is to investigate the association between current PPIs use and the development of COVID-19 as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Recently, four meta-analyses [ 31 – 34 ] were published regarding the association between the use of acid suppressants and COVID-19. Three meta-analyses [ 31 – 33 ] identified the relationship for PPIs and one by Kow et al [ 34 ] for famotidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, four meta-analyses [ 31 – 34 ] were published regarding the association between the use of acid suppressants and COVID-19. Three meta-analyses [ 31 – 33 ] identified the relationship for PPIs and one by Kow et al [ 34 ] for famotidine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, four meta-analyses [ 31 – 34 ] were published regarding the association between the use of acid suppressants and COVID-19. Three meta-analyses [ 31 – 33 ] identified the relationship for PPIs and one by Kow et al [ 34 ] for famotidine. Supplemental Table 5 describes the differences in study characteristics and the main results among the past meta-analysis and the present study.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis of six observational studies, current PPI users have a significantly higher risk of developing COVID-19 as well as dying from it. 76 Similarly, in another meta-analysis, which included twelve observational retrospective cohort studies, the poor outcome in PPI-using patients was quantified. 77 Also, a meta-analysis of four case-control studies and 10 cohort studies found a significantly enhanced risk of severity and mortality of COVID-19 infection in current users of PPIs.…”
Section: Adverse Effects-associated With Long-term Ppi Therapymentioning
confidence: 99%
“…In addition, long term PPI-use has been reported to be associated with increased risk of dementia, gastroenteritis, 60 , 61 acute 62–65 and chronic 66–68 kidney disease, pneumonia (eg, highest risk at 1 month regardless of dose), 69 mortality, 70 and more recently, COVID-19-associated mortality. 71 …”
Section: Clinical Outcomes For Gerd Treatmentmentioning
confidence: 99%